Investments in a Combined Energy Network Model: Substitution between Natural Gas and Electricity? - Jan Abrell; Hannes Weigt (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
Natural gas plays an important role in the future development of electricity markets, as it is the least emission-intensive fossil generation option and additionally provides the needed plant operating flexibility to deal with intermittent renewable generation. As both the electricity and the natural gas market rely on networks, congestion in one market may lead to changes in the other. In addition, investment in one market impacts investment in the other market to the extent that these investments may even become substitutes for each another. The objective of this paper is to develop a dynamic model representation of coupled natural gas and electricity network markets to test the potential interaction with respect to investments. The model is tested under simplified conditions as well as for a stylized European network setting. The results indicate that there is sufficient potential for investment substitution and market interactions that warrant the application of coupled models, especially with regard to simulations of long-term system developments.
Keywords: L94; L95; C63; 330; Electricity network; Natural gas network; Europe; MCP; Energiemarkt; Erdgasmarkt; Investition; Substitutionseffekt; Partielles Gleichgewicht; Europa